Temporal and spatial expression of cuticular proteins of Anopheles gambiae implicated in insecticide resistance or differentiation of M/S incipient species - Laura Vannini; Tyler W Reed; Judith H Willis (Parasites & Vectors, 2014)
Abstract Background Published data revealed that two of the 243 structural cuticular proteins of Anopheles gambiae, CPLCG3 and CPLCG4, are implicated in insecticide resistance and a third, CPF3, has far higher transcript levels in M than in S incipient species. We studied the distribution of transcripts for these three genes in the tissues of An. gambiae and the location of the proteins in the cuticle itself to gain information about how these cuticular proteins contribute to their important roles. Our data are consistent with CPLCG3/4 contributing to a thicker cuticle thus slowing penetration of insecticides and CPF3 possibly having a role in the greater desiccation tolerance of the M form. Methods Using RT-qPCR, we established the temporal expression of the genes and by in situ hybridization we revealed the main tissues where their mRNAs are found. Electron microscopy immunolocalization, using secondary antibodies labeled with colloidal gold, allowed us to localize these proteins within different regions of the cuticle. Results The temporal expression of these genes overlaps, albeit with higher levels of transcripts from CPF3 in pharate adults and both CPLCG3 and CPLCG4 are higher in animals immediately after adult eclosion. The main location of mRNAs for all three genes is in appendages and genitalia. In contrast, the location of their proteins within the cuticle is completely different. CPF3 is found exclusively in exocuticle and CPLCG3/4 is restricted to the endocuticle. The other CPF gene expressed at the same times, CPF4, in addition to appendages, has message in pharate adult sclerites. Conclusions The temporal and spatial differences in transcript abundance and protein localization help to account for An. gambiae devoting about 2% of its protein coding genes to structural cuticular proteins. The location of CPLCG3/4 in the endocuticle may contribute to the thickness of the cuticle, one of the recently appreciated components of insecticide resistance, while the location of CPF3 might be related to the greater desiccation resistance of the M form.